2011
DOI: 10.4236/wjns.2011.13008
|View full text |Cite
|
Sign up to set email alerts
|

The antinociceptive role of central arginine vasopressin is involved in the endogenous opiate peptide, serotonin and acetylcholine systems

Abstract: Our previous work has demonstrated that arginine vasopressin (AVP) plays a role in pain modulation. The present study investigated which kinds of neuropeptides and neurotransmitters in central nervous system might be involved in AVP antinociceptive role in the rat. The results showed that (1) intraventricular injection (icv) of V1 receptor antagonist [d(CH2)5Tyr(Me)AVP] and V2 receptor antagonist [d(CH2)5[D-Ile2, Ile4, Ala9-NH2]AVP] blocked the antinociceptive effect induced by AVP (icv), (2) the opiate recapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In addition, Li and colleagues showed that intracerebroventricular injection of AVP V 1 and AVP V 2 receptor antagonists blocked the antinociceptive effect induced by centrally administered AVP and further suggested that the analgesic effect of AVP involved endogenous opioidergic and cholinergic systems in the CNS [22]. Several studies have suggested that ACh may regulate the pain process.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Li and colleagues showed that intracerebroventricular injection of AVP V 1 and AVP V 2 receptor antagonists blocked the antinociceptive effect induced by centrally administered AVP and further suggested that the analgesic effect of AVP involved endogenous opioidergic and cholinergic systems in the CNS [22]. Several studies have suggested that ACh may regulate the pain process.…”
Section: Discussionmentioning
confidence: 96%